LIBERTATEA ȘI DEMNITATEA UMANĂ DIN PERSPECTIVĂ PAULINĂ (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
A Pauline Perspective on Human Dignity and FreedomHuman dignity and freedom are inalienable gifts of God to human beings, part of their ontological endowment, part of the image of God within them. Human freedom is the focus of Apostle Paul’s ethics, and it’s based on the principle of love, a principle springing from having the Holy Spirit that produces its own fruit (acc. to Galatians 5:13). Pauline freedom, as a path to perfection, is represented by the love towards one’s neighbour as a form of service (acc. to Romans 13:9). True freedom consists in the love that serves one’s neighbour, that is, the new way of life proposed by Apostle Paul is centred on Jesus Christ, who “has exemplary fulfilled the law and relies on the practice of virtue as a form of perfection.”